Adult patient with type 1 diabetes mellitus: Multiple factors to achieve an adequate control. Case report - Lizarzaburu Robles, Juan Carlos (2020)
Type 1 diabetes mellitus (T1DM) is one of the most common chronic childhood diseases. However, a large number of adult patients live with this condition. Insulin therapy is the cornerstone of diabetes treatment. Other important aspects are the promotion of a healthy lifestyle and the adhesion to medications. This is the case of a 29-year-old woman with a fifteenyear diagnosis of T1DM. Medical treatment and evolution over the last five years are described. The importance of new technologies such as continuous glucose monitoring and other factors such as adherence to treatment and family support were particularly important for the patient’s adequate disease control.